Knowledge, perception and attitude among pregnant mothers towards ibadah - Abdullah, Suhaiza; Ismail, Hamizah; Che Harun, Mazira; Abdul Rahim, Aidil Faszrul; Mustafa, Kamarul Bahyah; Sidek, Ayu Aszliana; Nusee, Zalina; Abd. Wahab, Noraziana (Faculty of Medicine, International Islamic University Malaysia, 2013)
To determine the knowledge, perception and attitude of pregnant mothers towards ibadah with regard to pregnancy and inpatient stay. All Muslim mothers admitted to antenatal ward of Hospital Tengku Ampuan Afzan, who agreed to participate were included in the study. Questionnaires were answered accordingly during her inpatient stay. Demographic data were collected and data entry and analysis performed using SPSS. Eighty patients( n=80) were enrolled into the study. About sixty percents (60%) had educational level of secondary school. Two third (n= 63,80%) mothers were from low parity (0-2). Approximately forty percents (40%) of mothers are admitted for latent phase of labour and premature contraction. About 45% were admitted due to other obstetric reasons. In the majority (87%), the length of stay was between 1 to 3 days. Half of the mothers (51%) did not pray during their stay. Sixty three percent of them admitted that they did not know that they should pray while in the ward. Three percent stated that they were shy while 5% indicated that they were uncomfortable to do so. These were in spite of the fact that the majority actually prayed five times per day at home. Only 13% gave the correct duration of nifas while 52% did not answer (most likely they did not know). The majority of the pregnant mothers have minimal knowledge regarding the need of solat during their hospital stay. Key words: Knowledge, perception, attitude, pregnant, ibadah